2020
DOI: 10.1063/10.0000538
|View full text |Cite
|
Sign up to set email alerts
|

The effect of sorption of air and hydrogen components on the structural characteristics of superconducting FeTe0.65Se0.35 single crystals

Abstract: X-ray studies of iron chalcogenide FeTe0.65Se0.35 single crystals were performed after they were exposed in air and hydrogen atmospheres at room and high temperatures, for long periods of time. It is found that impurity components have a significant effect on the structural characteristics of the diffraction pattern for this layered tetragonal superconducting material. It is shown that molecular impurities do not change the matrix symmetry of the tetragonal substitution solutions. However, when hydrogen molecu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
10
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
3
1

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(10 citation statements)
references
References 10 publications
0
10
0
Order By: Relevance
“…The transition is accompanied by strong lattice compression at which the crystal density increases by almost 15%. 19 22 In contrast to this expected behavior, we found that after the hydrogenation at temperatures of 180-250 °C, relaxation was practically absent (Fig. 2b).…”
Section: Structural Propertiesmentioning
confidence: 54%
See 4 more Smart Citations
“…The transition is accompanied by strong lattice compression at which the crystal density increases by almost 15%. 19 22 In contrast to this expected behavior, we found that after the hydrogenation at temperatures of 180-250 °C, relaxation was practically absent (Fig. 2b).…”
Section: Structural Propertiesmentioning
confidence: 54%
“…Since the volume of the crystal lattice decreases by about 15% after hydrogenation, 19 this leads to large chemical pressure effect. Hence, observed increase in the critical current density can be explained by the appearance of additional pinning centers due to significant mechanical stresses associated with the rearrangement of the crystal lattice after hydrogenation.…”
Section: Superconducting Propertiesmentioning
confidence: 99%
See 3 more Smart Citations